A biomimetic catalyst for electrocatalytic nitrogen to ammonia synthesis and a preparation method and application thereof
Patent Information
- Application Number
- CN202610070800.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-20
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-01-20
AI Technical Summary
以解决当前NRR反应中,非贵金属催化剂不能同时满足高转化率、高选择性和高稳定性的缺陷
本发明提供了一种电催化氮气合成氨气的仿生催化剂的制备方法,包括下列制备步骤:S1、将钼盐、铁盐、硫化钠以及尿素溶于水中,超声,得到前驱体溶液;S2、将泡沫镍进行预处理后,置于前驱体溶液中,反应,得到仿生催化剂。本发明采用廉价的铁盐为前驱体产生活性位点,钼盐作为助催化剂用于调控主催化剂Fe的电子转移。硫元素的给电子能力更强,以无机硫桥的方式取代了部分氧原子,用以加速催化剂内部Mo和Fe之间的电子的传输。
Smart Images

Figure CN121538679B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic ammonia synthesis technology, and in particular to a biomimetic catalyst for electrocatalytic nitrogen-to-ammonia synthesis, its preparation method, and its application. Background Technology
[0002] Ammonia (NH3) is a popular chemical raw material that plays an important role in human survival and development, and is widely used in industry and agriculture. It also possesses advantages such as high energy density, easy liquefaction, and convenient storage and transportation. As an important clean and carbon-free energy carrier, it can decompose to produce hydrogen. In terms of energy utilization, hydrogen energy has advantages such as being green, efficient, carbon-free, and having a wide range of applications. Currently, the main method for industrial synthesis of NH3 is the Haber-Bosch process (HB process). However, this process typically involves high temperatures (300-600°C). This is carried out under conditions of high pressure (20-40 MPa). Therefore, it results in a large amount of energy consumption and carbon dioxide emissions.
[0003] Electrocatalytic reduction of nitrogen to ammonia (NRR) is an emerging green ammonia synthesis technology with significant advantages over the traditional HB process. It can directly utilize electricity generated from renewable energy sources such as solar and wind power, achieving zero carbon emissions throughout the entire process. Operating at ambient temperature and pressure, it uses nitrogen (N2) from water and air as raw materials, avoiding the dependence on hydrogen in traditional processes. Numerous studies have shown that noble metal catalysts such as Au, Ru, and Pt are widely used in electrocatalytic reactions due to their strong surface binding energy and excellent conductivity. Their high catalytic activity can be attributed to the fact that the empty d orbitals of noble metal atoms can accept lone electrons from the N2 molecule to activate N2. N-bond. The N2 molecule has a high dissociation energy (940.95 kJ). The high cost and severe HER reaction (E0 = 0.000 V vs. RHE) make it difficult to activate and are generally considered the rate-determining step in the NRR process. On the other hand, its competing reaction, the hydrogen evolution reaction (HER) (E0 = 0.000 V vs. RHE), has a similar theoretical reduction potential to the NRR process (E0 = 0.092 V vs. RHE), resulting in low Faraday efficiency (FE). The high cost and severe HER reaction limit the industrial application of noble metal catalysts Au, Ru, and Pt. Therefore, developing non-noble metal or heteroatom-doped alloy catalysts with high ammonia yield and high Faraday efficiency has been a key focus and challenge in the field of electrocatalytic ammonia synthesis.
[0004] Transition metals, due to their abundant reserves and low prices, offer advantages suitable for large-scale industrial production, attracting considerable research interest. Furthermore, transition metals possess unoccupied d orbitals, which can accept lone pairs of electrons from N₂, weakening the electron density of N₂. The nitrogen triple bond lowers the reaction energy barrier. Among transition metals, Fe is the most widely distributed transition metal element in nature and plays an important role as an active center in electron transfer. In ecosystems, microorganisms rely mainly on Fe-containing proteases as electron carriers during nitrogen fixation, thereby activating nitrogen molecules. However, Fe-based catalysts also suffer from problems such as easy aggregation and corrosion. Therefore, designing non-noble metal catalysts with high conversion, high selectivity, and high stability remains a major challenge for NRR reactions. Summary of the Invention
[0005] The purpose of this invention is to provide a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen, its preparation method, and its application. This addresses the shortcomings of current non-precious metal catalysts in the NRR reaction, which cannot simultaneously achieve high conversion, high selectivity, and high stability.
[0006] To achieve the above objectives, the present invention provides a method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen, comprising the following preparation steps: S1. Dissolve molybdenum salt, iron salt, sodium sulfide and urea in water, and sonicate to obtain a precursor solution; S2. After pretreatment, the nickel foam is placed in a precursor solution and reacted to obtain a biomimetic catalyst.
[0007] In this invention, the molar ratio of molybdenum salt, iron salt, sodium sulfide and urea in S1 is 1:0.5-2:0.1-4:4.
[0008] In this invention, the molar volume ratio of molybdenum salt to water in S1 is 1 mmol: 100-200 mL.
[0009] In this invention, the molybdenum salt in S1 includes sodium molybdate, and the iron salt includes one of ferric chloride hexahydrate, ferric sulfate, and ferric nitrate nonahydrate, preferably ferric nitrate nonahydrate.
[0010] In this invention, the pretreatment process in S2 includes: washing the foamed nickel sequentially with acetone, hydrochloric acid and water to complete the pretreatment process.
[0011] In this invention, the mass concentration of hydrochloric acid is 30%-40%.
[0012] In this invention, the reaction temperature in S2 is 150-160°C. The reaction time is 6-8 hours.
[0013] In this invention, after the reaction in S2 is completed, the nickel foam is removed, washed with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst was obtained by drying at a certain temperature for 8 hours.
[0014] The present invention also provides a biomimetic catalyst prepared by the above-described method for preparing a biomimetic catalyst for electrocatalytic nitrogen-to-ammonia synthesis.
[0015] This invention also provides the application of the above-mentioned biomimetic catalyst in the electrocatalytic synthesis of ammonia from nitrogen.
[0016] like Figure 1 As shown, the principle of the biomimetic catalyst provided by this invention in the electrocatalytic synthesis of ammonia from nitrogen is as follows: Based on the synergistic effect of molybdenum-iron bimetallic compounds in biomimetic catalysis, the electrons enriched in the d orbitals of molybdenum-iron can generate σ coordination with the lone electrons of nitrogen, while the empty d orbitals can effectively transfer to N2. The antibonding orbitals provide sufficient holes, further weakening and activating the nitrogen-nitrogen triple bond. Driven by the electric field, the more electronegative S and O atoms provide the driving force for electron transfer, accelerating the hydrogenation of the intermediate.
[0017] In this invention, the biomimetic catalyst provided can also be used to construct small-scale, distributed ammonia production plants, particularly suitable for fertilizer production in remote areas. Secondly, it can convert intermittent renewable energy sources such as solar and wind power into ammonia, enabling long-term energy storage. Additionally, it can be used to treat nitrogen-containing wastewater, reducing nitrates to ammonia for recycling and environmental remediation. When transporting hydrogen, which is inconvenient to carry, easily transportable ammonia can be used as a hydrogen carrier, and hydrogen can be released through catalytic decomposition.
[0018] The present invention has the following beneficial effects: This invention provides a method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen, comprising the following steps: S1, dissolving molybdenum salt, iron salt, sodium sulfide, and urea in water, followed by sonication to obtain a precursor solution; S2, pretreating nickel foam, then placing it in the precursor solution and reacting to obtain the biomimetic catalyst. This invention uses inexpensive iron salt as the precursor to generate active sites, and molybdenum salt as a co-catalyst to regulate electron transfer in the main catalyst, Fe. Sulfur has a stronger electron-donating ability, replacing some oxygen atoms through inorganic sulfur bridges to accelerate electron transport between Mo and Fe within the catalyst.
[0019] This invention achieves in-situ growth of a catalyst on a nickel foam substrate via a one-step hydrothermal method, avoiding the agglomeration problem of traditional powder catalysts and improving catalyst stability. Furthermore, by adjusting the Mo... The Fe molar ratio and S doping amount optimize the electronic structure of the catalyst, enhance its adsorption and activation capacity for N2, and suppress the competitive hydrogen evolution reaction.
[0020] This invention uses inexpensive transition metals Fe and Mo as active components, reducing raw material costs by 90%. Furthermore, it employs a one-step hydrothermal method for preparation, resulting in a simple process that is easy to scale up for production.
[0021] The biomimetic catalyst MoFeS obtained by the preparation method of this invention x NF can be directly used as the working electrode cathode, eliminating the need for grinding, slurry preparation, coating, and other steps to prepare a current collector working electrode. At a reduction potential of -0.04 V vs RHE, the ammonia yield and Faraday efficiency reached 576.77%. cm 2 h and 80.01%. Furthermore, after 16 hours of continuous operation at this voltage (-0.04V vs RHE), the current density remained stable, and the biomimetic catalyst was used again in the NRR reaction to obtain 547.93 μg / cm³. 2 With an ammonia yield of 76.10% and a Faraday efficiency of 76.10%, the catalytic activity decreased by only 5%, demonstrating high catalytic activity, high selectivity, and excellent stability.
[0022] The technical solution of the present invention will be further described in detail below through embodiments. Attached Figure Description
[0023] Figure 1 This is a schematic diagram illustrating the principle of the biomimetic catalyst prepared in this invention in the electrocatalytic synthesis of ammonia from nitrogen. Figure 2 These are the XRD patterns of the biomimetic catalysts prepared in Examples 1-3; Figure 3 Here is a SEM image of the biomimetic catalyst prepared in Example 5; Figure 4 These are the Raman spectra of the biomimetic catalysts prepared in Examples 3-5 of this invention; Figure 5 These are impedance diagrams of the biomimetic catalysts prepared in Examples 4, 5, and Comparative Example 1 of this invention; Figure 6 This is the LSV diagram of the biomimetic catalyst prepared in Example 5 of this invention; Figure 7 It adopts the national standard GB T 5750.5-2023 NH4 produced by ultraviolet spectrophotometry + The concentrations were 0.1 mg. L, 0.5mg L, 0.7mg L, 1.0mg L, 1.5mg Calibration curve at L; Figure 8 This is a graph showing the ammonia yield and Faraday efficiency of the biomimetic catalyst prepared in Example 5 of this invention in the NRR reaction; Figure 9 This is a stability test diagram of the biomimetic catalyst It prepared in Example 5 of this invention; Figure 10 The MoFeS recovered by this invention x NF-5 (MoFeS after 16 hours of continuous operation) x NF-5) and fresh MoFeS x NF-5 (MoFeS undergoing the first NRR reaction) x A comparison of ammonia yield and Faraday efficiency in the NRR reaction of NF-5. Detailed Implementation
[0024] The present invention will be further described below with reference to embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by one of ordinary skill in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0025] Example 1 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 0.5 mmol of ferric chloride hexahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-1.
[0026] Example 2 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 0.5 mmol of ferric sulfate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-2.
[0027] Example 3 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 0.5 mmol of ferric nitrate nonahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-3.
[0028] Example 4 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 0.25 mmol of ferric nitrate nonahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-4.
[0029] Example 5 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 1 mmol of ferric nitrate nonahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-5.
[0030] Comparative Example 1 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 1 mmol of ferric nitrate nonahydrate, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-6.
[0031] Comparative Example 2 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 1 mmol of ferric nitrate nonahydrate, 3 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 8 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-7.
[0032] Comparative Example 3 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 1 mmol of ferric nitrate nonahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 160°C. The reaction was carried out for 24 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-8.
[0033] Comparative Example 4 A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen includes the following preparation steps: S1. Dissolve 0.5 mmol of sodium molybdate, 1 mmol of ferric nitrate nonahydrate, 2 mmol of sodium sulfide, and 2 mmol of urea in 70 mL of water. 25 The precursor solution was obtained by sonicating at a certain temperature for 20 minutes. S2, with a size of 1.2cm A 1cm piece of nickel foam was sequentially cleaned with acetone, 37% hydrochloric acid, and water, then placed in a precursor solution and reacted in a polytetrafluoroethylene reactor at 180°C. The reaction was carried out for 24 hours. After the reaction was completed, the nickel foam was removed, washed three times with water and ethanol, and then placed in a drying oven at 80°C. The biomimetic catalyst, denoted as MoFeS, was obtained by drying at a certain temperature for 8 hours. x NF-9.
[0034] Characterization test The biomimetic catalysts prepared in Examples 1-3 were observed by XRD, and the results are as follows: Figure 2 As shown. From Figure 2 It can be seen that FeMoS x In NF-3, 14.5, 32.3, and 40.2 correspond to the (002), (101), and (102) crystal planes of layered 2H-MoS2, respectively; and 32.9, 35.5, 40.3, 49.8, 57.4, 62.4, and 64.8 correspond to the (104), (110), (113), (024), (122), (214), and (300) crystal planes of Fe2O3, respectively. When ferric nitrate nonahydrate is used as the iron source, at the same hydrothermal temperature of 160... The lower layer is easier to decompose, which is more conducive to the growth of more Fe nanowire metal active sites on the NF substrate. In Example 1, ferric chloride hexahydrate contains Cl... - This may lead to catalyst poisoning, specifically manifested in the disappearance or weakening of the 2H-MoS crystal plane. When ferric sulfate is used as the iron source (Example 2), its high thermal decomposition temperature and low water solubility are unfavorable for the growth of iron atoms on NF, resulting in a low content of iron oxide at the active sites.
[0035] The biomimetic catalyst obtained in Example 5 was observed under a microscope, and its SEM image is shown below. Figure 3 As shown. From Figure 3 It can be seen that, due to the use of three-dimensional porous nickel foam (NF) as a substrate, the obtained FeMoS x The needle-like surface of NF-5 increases the number of active sites in contact with nitrogen, thus facilitating the NRR reaction.
[0036] The biomimetic catalysts obtained in Examples 3-5 were tested using Raman spectroscopy, and their Raman spectra are shown below. Figure 4 As shown. From Figure 4 It can be seen that when the Mo / Fe ratio is 1:1, i.e. in Example 3, there are obvious characteristic peaks of MoS2 and Fe2O3; when the amount of iron is further increased, and the Mo / Fe ratio is 1:2, i.e. in Example 5, the Raman signal intensity of MoS2 gradually weakens; when the amount of iron is reduced, and the Mo / Fe ratio is 1:0.5, i.e. in Example 4, the peak area of Fe2O3 is smaller.
[0037] The impedance of the biomimetic catalysts obtained in Examples 4 and 5 and Comparative Example 1 was tested. The impedance voltage was the open-circuit voltage, and the frequency ranged from 0.01 Hz to 100 kHz. The results are as follows: Figure 5 As shown. From Figure 5 It can be seen that when the molar ratio of sodium molybdate to sodium sulfide is large, and when sodium sulfide is not added, the resulting biomimetic catalyst has a larger impedance.
[0038] The ammonia yield (YNH4) was tested when the biomimetic catalysts prepared in Examples 1-5 and Comparative Examples 1-4 were used as self-supporting electrodes. + The parameters were: ) and Faraday efficiency (FE). A Koster CS310X electrochemical workstation was used. The working electrode was the self-supporting electrode prepared in Examples 1-5 and Comparative Examples 1-4; the counter electrode was a platinum wire electrode; and the reference electrode was Ag. AgCl, electrolyte is 0.05 mol The results of the L H2SO4 solution are shown in Table 1.
[0039] Table 1. Test results of ammonia yield and Faraday efficiency
[0040] Because Comparative Example 4 is at 180 The reaction time was too high (24 hours), and the temperature and reaction time were too long, resulting in the breakage of the biomimetic catalyst, which could not be used as a self-supporting electrode.
[0041] As shown in Table 1, the ammonia yields from highest to lowest are MoFeS x NF-5>MoFeS x NF-3>MoFeS x NF-4, Faraday efficiency from highest to lowest is MoFeS x NF-4>MoFeS x NF-3>MoFeS x NF-5. This is because the Raman characteristic peak area of Fe2O3 in Example 4 is relatively small ( Figure 4 Therefore, there are fewer active sites for activating nitrogen, resulting in a lower ammonia yield of 381.66 μg / cm³. 2 / h, but at the same time the hydrogen evolution reaction was also suppressed, resulting in a Faraday efficiency of 94.05%. Example 3 shows obvious characteristic peaks of MoS2 and Fe2O3 ( Figure 4 At this point, the ammonia yield increases, but the competing reaction leads to a decrease in Faraday efficiency. In Example 5, the Raman signal intensity of MoS2 gradually weakens ( Figure 4 At this point, the ammonia yield increased to 576.77 μg / cm³. 2 However, the hydrogen evolution reaction was severe, causing the Faraday efficiency to decrease to 80.01%. When sodium sulfide was not used (Comparative Example 1), the ammonia yield and Faraday efficiency were 132.41 μg / cm³. 2 / h and 36.15%. This is mainly due to the efficient conversion of the d-electron orbitals of molybdenum and iron to N2. Antibonding orbitals provide ample holes, significantly weakening and elongating the nitrogen-nitrogen triple bond. In Example 5, the molar ratio of sodium molybdate to sodium sulfide was adjusted to 1:4. At this point, sulfur acts as a sulfur bridge, facilitating electron transport in the Mo / Fe mixture, resulting in a significant improvement in conductivity. Consequently, the ammonia yield and Faraday efficiency were greatly enhanced. In Comparative Example 2, the sulfur doping was further increased, with the molar ratio of sodium molybdate to sodium sulfide reaching 1:6. In this case, the excessive MoS2 layer physically covers the active sites on the iron surface, preventing N2 molecules from effectively contacting the catalyst surface, thus drastically reducing the ammonia yield.
[0042] The LSV diagram of the biomimetic catalyst obtained in Example 5 as a self-supporting electrode under Ar and N2 atmospheres is shown below. Figure 6 As shown. From Figure 6 It can be seen that the current density when N2 is introduced is greater than the current density when Ar is introduced, indicating that the FeMoS2 phase is more stable when N2 is introduced. x An electrocatalytic reduction of N2 occurred on / NF-5, generating additional current.
[0043] NH4 prepared by the national standard ultraviolet spectrophotometry + The concentrations were 0.1 mg. L, 0.5mg L, 0.7mg L, 1.0mg L, 1.5mg The calibration curve at L, such as Figure 7 As shown.
[0044] When the biomimetic catalyst obtained in Example 5 was used as a self-supporting electrode, the NRR was tested using the It method. Different reduction voltages were applied from 0.06V vs. RHE to -0.44V vs. RHE, with a scan time of 1 h. The obtained ammonia yield (Yield) and Faradaic efficiency (FE) are as follows: Figure 8 As shown.
[0045] from Figure 8 It can be seen that N2 is not easily activated when the reduction voltage is low, and the hydrogen evolution effect increases when the reduction voltage is more negative, leading to a decrease in ammonia yield and Faraday efficiency. The optimal reduction voltage is -0.04V vs. RHE, achieving an ammonia yield and Faraday efficiency of 576.77. cm 2 h and 80.01%.
[0046] The biomimetic catalyst (MoFeS) obtained in Example 5 x Using NF-5 as a self-supporting electrode, its It stability was tested at a reaction voltage of -0.04V vs. RHE, and the results are as follows: Figure 9 As shown. From Figure 9 It can be seen that the current density remains stable even after 16 hours of continuous operation.
[0047] After running for 16 hours, the above-mentioned biomimetic catalyst was recovered to obtain the recovered MoFeS x NF-5, followed by the recovery of MoFeS x NF-5 is used in the NRR reaction. It also reacts with MoFeS. x NF-5 during its first NRR (fresh MoFeS) x A comparison was made between the ammonia yield and Faraday efficiency of NF-5, and the results are as follows: Figure 10 As shown. From Figure 10 It can be seen that after 16 hours of continuous operation, the recovered MoFeS x NF-5 still has a concentration of 547.93 μg / cm³. 2 Ammonia yield of / h and Faraday efficiency of 76.10%. Fresh MoFeS x NF-5 (MoFeS undergoing the first NRR reaction) x NF-5) has 576.77 μg / cm³ 2 The ammonia yield was 80.01% per hour and the Faraday efficiency was 80.01%. Compared to the former, the ammonia yield (catalytic activity) decreased by only 5% after 16 hours of cycling.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a biomimetic catalyst for the electrocatalytic synthesis of ammonia from nitrogen, characterized in that, The preparation steps include the following: S1. Dissolve molybdenum salt, iron salt, sodium sulfide and urea in water, and sonicate to obtain a precursor solution; S2. After pretreatment, the nickel foam is placed in a precursor solution and reacted to obtain a biomimetic catalyst. The molar ratio of molybdenum salt, iron salt, sodium sulfide, and urea in S1 is 1:0.
5. 2:0.1-4:4; The molar volume ratio of molybdenum salt to water in S1 is 1 mmol: 100-200 mL; S1 contains molybdenum salts including sodium molybdate, and iron salts including one of ferric chloride hexahydrate, ferric sulfate, and ferric nitrate nonahydrate. The pretreatment process in S2 includes: washing the nickel foam sequentially with acetone, hydrochloric acid, and water to complete the pretreatment process; the mass concentration of hydrochloric acid is 30%-40%. The reaction temperature in S2 is 150-160℃, and the reaction time is 6-8h.
2. The biomimetic catalyst prepared by the method for preparing an electrocatalytic nitrogen-to-ammonia synthesis biomimetic catalyst as described in claim 1.
3. The application of the biomimetic catalyst according to claim 2 in the electrocatalytic synthesis of ammonia from nitrogen.
Citation Information
Patent Citations
Iron-molybdenum doped nickel sulfide / foamed nickel electrode and preparation method and application thereof
CN114016050A
FeMo co-doped nickel sulfide nanosheet as well as preparation method and application thereof
CN118756212A